Algorithms, blockchain & cryptocurrency : implications for the future of the workplace - Brown, Gavin; Whittle, Richard (Future of Work Ser., 2020)
The convergence of Algorithms, Blockchain and Cryptocurrency (ABC) has the potential to fundamentally disrupt the current world of work. This book investigates the effects of this on the worker, the organisation and the economy, by considering a future where the traditional power relationships between workers and firms no longer apply.